Improving Public Speaking Competence for the Students of SMA Al Washliyah 1 Medan - Lubis, Fatma Wardy; Moulita; M, Munzaimah; Sutatminingsih, Raras (Talenta Publisher, 2025)
Public speaking competence is needed in various interactions between people, both in personal and social contexts, including leadership, business, religion, law, education, and others. In the field of education, for example, the need for public speaking skills especially for students is very necessary. The ability to speak in public is very helpful in increasing students' self-confidence which can support their performance both in education and social life. This ability is not only to encourage students to excel in the academic field within their school, but also to excel in other fields outside of school. As an implementation in helping to improve students' public speaking skills, the FISIP USU service team has carried out public speaking training service activities in one of the schools in Medan City, namely SMA Al Washliyah 1 in September 2023. The service team provided provision for students to be more capable of communicating in front of the public. Participants received public speaking materials and some of them practiced public speaking directly in a competition. This service activity is a form of contribution to the implementation of the fourth point of Sustainable Development Goals, namely Quality Education.